Two Digital-scalar PWM Schemes for Generating ree-phase Unbalanced Voltages - Darlan A. Fernandes; Euzeli C. Santos Jr; Fabiano F. Costa; Alexandre C. Castro (Eletrônica de Potência)
This paper presents two modulation approaches for generating unbalanced voltages by means of four-leg voltage source inverters (VSI). The first modulation is an extended scheme of a digital scalar pulse width modulation previously proposed for controlling three-leg inverters. The second one is based on the decomposition of the voltage reference signals into their symmetrical components. The schemes are compared theoretically, by simulations and by experimental results. As consequence, it is found out a total equivalence between the two modulations despite their different inspirations. The fundamentals of both techniques and a mathematical proof of their equality are unfolded. Also, the performance of the techniques with respect to the harmonic distortion and power switching loss are discussed. The results show that the techniques are effective.